Penguatan Resiliensi Beragama pada Anak Muallaf di Kala Wih Ilang Takengon - Izzatur Rusuli; Zakiul Fuady; Ali Mustafa (Prodi Ekonomi Syariah Universitas Pamulang, 2024)
Religious conversion is not a new phenomenon in society, especially in the diverse nation of Indonesia. Interestingly, there are several Karo children in Kala Wih Ilang Takengon whose parents or extended families still adhere to their traditional beliefs, but the children have converted to Islam. This community service aims to strengthen the resilience of these young converts, ensuring they remain steadfast in their new faith, and to promote religious moderation. The approach used is Community Based-Research (CBR), which involves treating the supported children as partners in the service project. The steps taken include a pre-assessment activity involving site observation, an assessment to gather information from stakeholders about the children's conditions, and the implementation of the service, which includes providing reinforcement of resilience and religious moderation. The results of this service show that five young converts were supported: Hevi Harpani, Febrina, Marsella, Rivaldo Ginting, and Alex Barus. Currently, they are spread across Islamic boarding schools in Takengon and Aceh Besar. Strengthening resilience and religious moderation was conducted through a personal approach, using question-and-answer sessions and discussions related to the topics to be reinforced. Additionally, the service team provided gifts such as prayer equipment and reading materials to help the supported children remain consistent in their Islamic faith and practice it moderately. This community service recommends that local governments provide attention and support to these children so they can pursue their education. Keywords: muslim convert children, religious moderation, reinforcement, resiliency